Spectrophotometric and HPLC Methods for Simultaneous Estimation of Roxithromycin and Ambroxol from Tablets - Roset Shobana, Esther; Sivasubramanian, Lakshmi (Asian Journal of Chemistry, 2010)
A simple, accurate, economical and reproducible UV spectrophotometric and a HPLC method for simultaneous estimation of two-component drug mixture of roxithromycin and ambroxol in combined tablet dosage form have been developed. The first developed method employs multiwavelength spectroscopy using six mixed standards and 267 nm and 245 nm as two wavelengths for estimation. Linearity was observed in concentration range of 50-300 μg/mL of roxithromycin and 10-60 μg/mL of ambroxol. Developed HPLC method is reversephase chromatographic method using Hypersil C18 column and acetonitrile:water in the ratio of 35:65 v/v pH 5.0 as mobile phase. For HPLC method, linearity was observed in concentration range of 100 -500 μg/mL of roxithromycin and 20-100 μg/mL of ambroxol. Results of analysis were validated statistically and by recovery studies.